If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(z + 2) + -2z = -17 Reorder the terms: 9(2 + z) + -2z = -17 (2 * 9 + z * 9) + -2z = -17 (18 + 9z) + -2z = -17 Combine like terms: 9z + -2z = 7z 18 + 7z = -17 Solving 18 + 7z = -17 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 7z = -17 + -18 Combine like terms: 18 + -18 = 0 0 + 7z = -17 + -18 7z = -17 + -18 Combine like terms: -17 + -18 = -35 7z = -35 Divide each side by '7'. z = -5 Simplifying z = -5
| -15=.50(x+6) | | 7w+5-3+-2w=4w-6+w+8 | | 2x-3+x-10=20 | | 2x-3x+532= | | 43=n-6 | | 4ln(x)-8=0 | | 83=m-10+14-1-7 | | 8w+5z=x+3 | | 9a-5=2a+5 | | 0=16t^2-48t+64 | | 9.8*.06= | | -0.25y+4=1 | | 58+z=87 | | X=8x+17 | | (2x-4)(3x+8)=0 | | 238=14t | | -2x+12=x-4+x | | W+11=100 | | -16t^2-18t+210=0 | | (X-6)(y+8)=0 | | 4=80-q | | f(x)=-0.06x^3+18x^2+800x-5000 | | 4y^2=50 | | -5+4y=53 | | -1=4(w-4)-7w | | 2x+6-5x=14-14x+11x-8 | | 4m^3-21m-18=0 | | 3+4(2-x)=3x+(-x-7) | | 19z=95 | | X^2+10w-2=0 | | 0.12(18)+0.002X=0.06(12+X) | | 24-4(2-x)=0 |